2020
DOI: 10.1111/jdi.13388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for diabetic neuropathy and painful diabetic neuropathy in primary and secondary healthcare in Qatar

Abstract: Aims/Introduction: This study determined the prevalence and risk factors for diabetic peripheral neuropathy (DPN) and painful DPN (pDPN) in patients with type 2 diabetes in primary healthcare (PHC) and secondary healthcare (SHC) in Qatar. Materials and Methods: This was a cross-sectional multicenter study. Adults with type 2 diabetes were randomly enrolled from four PHC centers and two diabetes centers in SHC in Qatar. Participants underwent assessment of clinical and metabolic parameters, DPN and pDPN. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…Late diagnosis of DN can lead to significant morbidity in the form of diabetic foot ulceration and amputation and increased mortality. 5 Therefore, it is recommended that all patients should be screened for DN when T2DM is diagnosed. 6 Peripheral nerve conduction velocity (NCV) detection is the most sensitive, accurate and reliable method for diagnosing DN.…”
Section: Introductionmentioning
confidence: 99%
“…Late diagnosis of DN can lead to significant morbidity in the form of diabetic foot ulceration and amputation and increased mortality. 5 Therefore, it is recommended that all patients should be screened for DN when T2DM is diagnosed. 6 Peripheral nerve conduction velocity (NCV) detection is the most sensitive, accurate and reliable method for diagnosing DN.…”
Section: Introductionmentioning
confidence: 99%
“…Fasting plasma glucose was demonstrated to be an independent factor associated with PDN in a previous study [21]. Some studies have indicated that poor glycaemic control was not associated with PDN [26,37], whereas other studies found that HbA1C and pain severity were associated [14]. An interesting discovery from the SCOPE research is that differences in blood glucose level parameters impact on pain severity between newly diagnosed PDN and participants with a previous diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…In a German educational initiative, painful and painless DSPN were previously undiagnosed in 57 and 82% of the participants with type 2 diabetes, respectively 17 . Likewise, in cross-sectional studies in Qatar, 80% of type 2 diabetes patients with DSPN reported that they had previously not been diagnosed with or treated for this condition 18,19 . Underdiagnosis and hence underestimation of DSPN was also frequent in South-East Asia, possibly due to a lack of consensus on screening and diagnostic procedures 20 .…”
Section: Introductionmentioning
confidence: 99%